Application of MALDI MS imaging after sequential processing of latent fingermarks. (February 2021) - Bradshaw, R.; Wilson, G.; Denison, N.; Francese, S.
Graphical abstract: Highlights: MALDI MSI is compatible with latent (natural) fingermark sequential processing. Sequential processing still leaves molecules that can be imaged by MALDI MSI. MALDI MSI "fills in the gaps" left by conventional fingermark enhancement techniques. The application of MALDI MSI following sequential processing yields higher ridge pattern coverage on brown tape. Abstract: Latent fingermarks are routinely visualised by subjecting them to one or more CSI/crime lab processes to maximise the recovery of ridge flow and minutiae permitting an identification. In the last decade mass spectrometric imaging (MSI) techniques have been applied to fingermarks to provide information about a suspect and/or on the circumstances of the crime as well as yielding additional images of the ridge pattern. In some cases, these techniques have shown the ability to provide further ridge detail, "filling in the gaps" of the developed mark. Matrix Assisted Laser Desorption Ionisation Mass Spectrometry Imaging (MALDI MSI) is presently the most advanced of the so-called 'surface analysis' techniques, in terms of compatibility with a number of fingermark enhancement processes and implementation in operational casework. However, for the use of this technique in major crimes to become widespread, compatibility with sequential processing must be demonstrated. This short study has assessed compatibility with a number fingermark processing sequences applied to natural marks on the adhesive side of brown (parcel) and clear tapes. Within the study undertaken, the results confirm the possibility to use MALDI MSI in sequence with multiple processes offering in some instances, complementary ridge detail with respect to that recovered from marks developed by conventional sequence processing.